2012
DOI: 10.1095/biolreprod.111.096206
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Human Endometrium1

Abstract: Autophagy appears to play an important role in the normal development and maintenance of homeostasis in a variety of tissues, including the female reproductive tract. However, the role of autophagy and the association between autophagy and apoptosis in cyclic remodeling of the human endometrium have not been described. Therefore, we investigated the involvement of autophagy during the human endometrial cycle and its association with apoptosis. Endometrial samples were obtained from 15 premenopausal, nonpregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 42 publications
5
60
0
2
Order By: Relevance
“…It has been reported that the induction of autophagy exerts a proapoptotic effect on normal human endometrial cells (Choi et al 2012). Compared with normal endometria, a remarkable activation of the autophagic process was observed in ectopic endometrial lesions (Nasu et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the induction of autophagy exerts a proapoptotic effect on normal human endometrial cells (Choi et al 2012). Compared with normal endometria, a remarkable activation of the autophagic process was observed in ectopic endometrial lesions (Nasu et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…These steroids are the two central balancing factors in the human endometrium (21,22). Indeed, the induction of autophagy in endometrial cells treated with estrogen alone (the proliferative phase) increased with the addition of progesterone (the secretory phase) and with the removal of estrogen and progesterone…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that the induction of autophagy exerts a proapoptotic effect on normal human endometrial cells (21). However, autophagy is suppressed in endometriotic cells due to derepression of mammalian target of rapamycin (mTOR), a major negative regulator of autophagy, which results in decreased endometriotic cell apoptosis (22).…”
mentioning
confidence: 99%
“…In human endometrial cells, autophagy seems to be involved in the cell cycle (Choi et al 2012). However, whether ovarian steroid hormones regulate autophagic response in the mouse uterus has not been established.…”
Section: Introductionmentioning
confidence: 99%